The effect of sex, age and performance level on pacing of Ironman triathletes - Knechtle, B.; Käch, I.; Rosemann, T.; Nikolaidis, P. T. (Research in Sports Medicine, 2019)
The aim of the present study was to examine the effect of sex, age and performance level on pacing of Ironman triathletes. Split times (i.e. swimming, cycling, and running) and overall race times of 343,345 athletes competing between 2002 and 2015 in 253 different Ironman triathlon races were analyzed. Participants were classified into nine performance groups according to their overall race time. Times in swimming, cycling, running and transition were expressed as percentage of the overall race time. Women spent relatively less time (%) in swimming, running and transition time, and more time (%) in cycling than men (p < 0.001). The fastest performance group was relatively faster in running (34.8 ± 1.4 versus 40.3 ± 3.0%, Eta2= 0.098) and transition time (0.9 ± 0.3 versus 2.2 ± 0.6%, Eta2= 0.178), and relatively slower in swimming (10.2 ± 0.8 versus 9.8 ± 1.5%, Eta2= 0.018) and cycling (54.1 ± 1.4 versus 47.8 ± 2.8%, Eta2= 0.138) than the slowest performance group (p < 0.001). The younger age groups were relatively faster in swimming, running and transition time, but relatively slower in cycling. In summary, the fastest Ironman triathletes were the relatively fastest in running and transition times. Thus, race tactics in an Ironman triathlon should focus on saving energy during swimming and cycling for the running split.